Transgene inheritances and genetic similarities of near isogenic lines of genetically modifi ed common beans - Pinheiro, Patrícia Valle; Faria, Josias Corrêa de; Nogueira, Elsa Oliveira Paranaguá e Lago; Aragão, Francisco José Lima (Pesquisa Agropecuaria Brasileira, 2010)
The objective of the present work was to determine the inheritance and stability of transgenes of a transgenic bean line expressing the genes rep-trap-ren from Bean golden mosaic virus and the bar gene. Crosses were done between the transgenic line and four commercial bean cultivars, followed by four backcrosses to the commercial cultivars. Progenies from each cross were evaluated for the presence of the transgenes by brushing the leaves with glufosinate ammonium and by polymerase chain reaction using specific oligonucleotides. Advanced generations were rub-inoculated with an isolate of Bean common mosaic necrosis virus (BCMNV). The transgenes were inherited consistently in a Mendelian pattern in the four crosses studied. The analyzed lines recovered close to 80% of the characteristics of the recurrent parent, as determined by the random amplified DNA markers used, besides maintaining important traits such as resistance to BCMNV. The presence of the transgene did not cause any detectable undesirable effect in the evaluated progenies.